2006
DOI: 10.1016/j.virol.2005.09.023
|View full text |Cite
|
Sign up to set email alerts
|

CTL escape and increased viremia irrespective of HIV-specific CD4+ T-helper responses in two HIV-infected individuals

Abstract: We investigated whether development of mutations leads to loss of CD8 T-cell recognition in HIV-1 infection and is possibly linked to alterations in HIV-1-specific CD4(+) T-cell responses in 2 HIV-infected individuals. In patient, H434 full genome sequencing of HIV-1 biological clones at early and late time points during disease progression showed development of fixed mutations in 16 predicted HIV-specific CTL epitopes. Loss of T-cell recognition and reactivity against wild-type and mutant epitopes was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…During viral escape from the B27-KK10 response, the L 268 M substitution develops significantly earlier than mutations at codon 264 (17,22,33,52). Rather than functioning as a compensatory mutation, however, this L 268 M mutation appears to represent an early partial escape mutation at a TCR contact residue (38, 52) and has little impact on the replicative capacity of HIV-1 (52).…”
Section: Discussionmentioning
confidence: 99%
“…During viral escape from the B27-KK10 response, the L 268 M substitution develops significantly earlier than mutations at codon 264 (17,22,33,52). Rather than functioning as a compensatory mutation, however, this L 268 M mutation appears to represent an early partial escape mutation at a TCR contact residue (38, 52) and has little impact on the replicative capacity of HIV-1 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Patients were included in the study only if their CD4 counts were above 300 cells per mm 3 at the time of enrollment and if they had been on continuous antiretroviral therapy (ART) with a plasma viral load of less than 50 copies per ml for at least 6 months. Although these patients were followed for an average of 14 months, for the present study, only data from a sample taken toward the end of the study (i.e., while the patients remained off treatment) were (18,19,24,28,37). For each mutation, the average time between infection and escape in HLA-matched hosts (the reciprocal of the escape rate) and the average time between infection and reversion in HLAmismatched hosts are provided.…”
Section: Methodsmentioning
confidence: 99%
“…Mutations at each of these sites have previously been shown to confer escape in vitro (18,19,24,28,37). The rates at which they escape in HLA-matched hosts and revert in HLA-mismatched hosts, as measured from a longitudinal cohort of 189 acute seroconverters, are presented in Table 1.…”
mentioning
confidence: 99%
“…With the increased feasibility of screening for genome-wide CTL responses (1,5,9,22,26,59,67) and sequencing of HIV-1 (58,60), numerous studies have undertaken comprehensive analyses to examine the interplay between host CTL responses and the evolution of HIV-1 (2,10,16,21,30,31,36,39,53,65). In particular, two studies investigated HIV-1 sequence variations across the entire genome and revealed a strong influence of CTL-driven immune responses on HIV-1 evolution both within the first month and many years after infection (2,10).…”
mentioning
confidence: 99%